Antimicrobial effect of Uthamadi Choorna during Ksharasutra Therapy in Bhagandara (International Journal of Ayurveda and Pharma Research, 2023)
In the modern era, ano rectal diseases are increasing day by day due to the changes in life style especially the food habits. Fistula in ano is one among them. It is a chronic illness which is, though not fatal but quite discomforting and troublesome to the patient and often puts a deep impact on the quality of life of a patient. Fistula in ano is a track lined by granulation tissue which connects peri anal skin superficially to anal canal, ano rectum or rectum deeply. The main clinical symptoms consist of pain, swelling and pus discharge. Due to higher recurrence rate and postoperative complication, fistula-in-ano is a headache in current surgical practice. Bhagandara which is described in Ayurveda classics can be correlated with Fistula in ano. Ksharasuthra therapy is a parasurgical procedure in Ayurveda which is found more effective in the management of fistula in ano. Even after Ksharasuthra application, pus discharge from fistulous tract delays the healing and makes the post operative period more difficult. So there is a need a of some adjuvant drug which can manage these problems in a better way and promote healing process by reducing the microbial load.Uthamadi Choorna is mentioned in Bhagandara prathishedha adhyayam in Ashtamga hrdaya and it contains Guggulu, Thriphala, Khadira and Asana which are having various chemical constituents that showed antimicrobial activity in pharmacological studies. The objective of the present study is to evaluate the antimicrobial effect of Uthamadi choorna during Ksharasuthra therapy in Bhagandara.